Kinetics of Cu, Pb and Zn removal during soil flushing with washing agents derived from sewage sludge - Barbara Klik (Nature Portfolio, 2021)
Abstract This paper presents the first tests of Cu (7875 mg/kg), Pb (1414 mg/kg) and Zn (566 mg/kg) removal from contaminated soil with sewage-sludge–derived washing agents (SS_WAs) (dissolved organic matter, DOM; soluble humic-like substances, HLS; soluble humic substances, SHS) and Na2EDTA (as a standard benchmark) in column experiments. Flow rates of 0.5 ml/min and 1 ml/min were used. Using a 1. order kinetic model, the kinetic constant (k), the maximum concentrations of each metal removed (C max), and the initial rates of metal removal (r) were established. At both flow rates, stable flow velocity was maintained for approximately eight pore volumes, for flushing times of 8 h (1.0 ml/min) and 16 h (0.5 ml/min). Although the flow rate did not influence k, it influenced C max: at 1 ml/min, C max values were higher than at 0.5 ml/min. For Cu and Zn, but not Pb, k was about twofold higher with Na2EDTA than with SS_WAs. Although Na2EDTA gave the highest k Cu, C max,Cu was highest with DOM (Na2EDTA, 66%; DOM 73%). For Pb removal, HLS was the most effective SS_WA (77%; Na2EDTA was 80% effective). k Zn was about twofold higher with Na2EDTA than with SS_WAs. C max,Zn was highest with HLS. The quick mobilization of Cu, Pb and Zn with most of the WAs corresponded to efficient metal removal from the exchangeable (F1) fraction.